Pengaruh Remunerasi dan Motivasi terhadap Kinerja Tenaga Administrasi PNS dan Non PNS Universitas Brawijaya - Geonardo, Derian Surya Setiawan; Haryono, Bambang Santoso; Hanafi, Imam (Jurnal Ilmiah Administrasi Publik, 2021)
Remuneration policy is born in order not to occur the overlap of income between education, where previously the education of civil servants more income and have more activities than with permanent education Non PNS. This research aims to analyse partial remuneration influence and partial motivation, then the simultaneous influence of remuneration and motivation to the performance of civil servants and non-civil servants at the Faculty of Computer Science of Brawijaya University. This research uses quantitative methods with the method of data collection in the form of a questionnaire. Method of data analysis using SPSS Vr. 24 program. Based on the results of the research came the conclusion that the results of the hypothesis test Fcountdown > Ftabel is 22,976 > 3,204 significance F of < Alpha (0,000 < 0,05) remuneration significantly affects the performance of employees, while motivation also significantly affects the performance of employees.